Life-cycle water uses for energy consumption of Chinese households from 2002 to 2015. (1st February 2019) - Liao, Xiawei; Chai, Li; Ji, Junping; Mi, Zhifu; Guan, Dabo; Zhao, Xu
Abstract: China's household energy demands' life-cycle water uses from 2002 to 2015 are quantified with an Input-Output analysis disaggregating rural and urban impacts. 9.73 and 1.60 km 3 of water was withdrawn and consumed respectively in the life cycle of Chinese household energy demands in 2015, which was dominated by power and heat uses. An average urbanite's household energy uses, including coal, gas, petroleum products, power and heat, require about four times of life-cycle water uses than its rural counterpart. Among all upstream sectors, while agricultural sectors accounted for the largest shares for all energy uses, oil and gas extraction made significant contributions to petroleum products and gas consumption. A Structural Decomposition Analysis is conducted to disentangle the impacts of four driving factors, i.e. population, demand, economic structure and technology. Population change reduced energy consumption's life-cycle water use for rural households but increased that for urban households. Each economic sector's water intensity decreases, which represent technology advancement, played the dominant role curbing household energy consumption's life-cycle water uses. While power and heat dominates the household energy use profile, urbanization is accompanied by household consumption shifting from coal to gas and petroleum products. In order to reduce household energy consumption's impacts and reliance on water resources, it is imperative to reduce energy production's water use by adopting water-saving technologies, such as air cooling, as well as to reduce upstream sectors' water intensities, such as by promoting drip irrigation. Highlights: Household energy demands' life cycle withdrew 9.73 km 3 of water in 2015. Urban households' energy demands use 4 time water than rural ones. Agriculture contributed the most to final energy demands' upstream water uses. Technology has offset the most water uses for household energy demands.